The effect of additional postural neck muscle control on conventional physiotherapy rehabilitation in reducing shoulder pain and disability in recreational surfers - I Putu Yudi Pramana Putra; M. Widnyana; I Dewa Gede Alit Kamayoga; Anak Agung Gede Eka Septian (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: Shoulder pain and disability is a disorder commonly experienced by surfers, which is characterized by pain and limitations in the shoulder region when performing functional movements. Shoulder movement is closely related to the surfer's paddling movements when surfing, so high paddling intensity increases the risk of complaints in the shoulder region. This research aimed to prove that adding postural muscle neck control to conventional physiotherapy rehabilitation intervention was more effective in reducing shoulder pain and disability than conventional physiotherapy rehabilitation intervention. Methods: This research was experimental with a randomized pre- and post-test two-group design. Research participants were randomly divided into two groups. This research measured shoulder disability using the shoulder pain and disability index (SPADI) questionnaire. Results: The paired T-test analysis showed significant differences in the reduction in SPADI scores in group intervention, which was 23.2±2.7 with p-value< 0.001, and in group control, was 20.15± 3.3 with p-value< 0.001 in the patient's shoulder functional increase. The independent T-test obtained a p-value of 0.002, proving a significant difference between the intervention and control groups in reducing shoulder disability among recreational surfers. Conclusion: There were significant differences in SPADI scores before and after both group interventions. In addition, data showed that the additional postural neck muscle exercise on conventional physiotherapy rehabilitation obtained better improvement in shoulder disability than conventional physiotherapy intervention only among recreational surfers. Keywords: Conventional physiotherapy rehabilitation, postural muscle neck control, recreational surfers, shoulder pain and disability